The Culture of Criticism and the Criticism of Culture. - Gunn, Giles (Oxford University Press, 1988)
The aim of this book is to challenge the assumptions made by the structuralist and post-structuralist schools of literary criticism. It defends and attempts to re-evaluate the kind of moral reflection associated with the critical legacy of such writers as Lionel Trilling and Edmund Wilson.